Hydrophobic edible composite packaging membrane based on low-methoxyl pectin/chitosan: Effects of lotus leaf cutin. (December 2020) - Ye, Yanqi; Zeng, Fansen; Zhang, Meiqing; Zheng, Shiyu; Li, Jie; Fei, Peng
Graphical abstract: Highlights: Cutin enhanced membranes hydrophobicity, made contact angle from 61.8° to 90.3°. Cutin reduced water absorption and enhanced water vapour permeability of membranes. Cutin enhanced membranes tensile strength and elongation at break within limits. The incorporation of lotus leaf cutin enhanced the thermal stability of membranes. Abstract: In this study, cutin extracted from lotus leaf was incorporated with low-methoxy pectin and chitosan to prepare hydrophobic edible composite membranes. Results showed that the formation and microstructure of the membranes were affected by the addition of lotus leaf cutin, which filled the gap between chitosan and low-methoxyl pectin. This addition results in obvious changes in the composite packaging membranes and weakens crystal peaks. According to the contact angle measurement, the hydrophobicity of composite packaging membranes was enhanced by the addition of lotus leaf cutin increasing the contact angle from 61.8° to 90.3°. With the increased cutin addition from 0 g to 3 g, water absorption was significantly decreased from 48.83 % to 41.64 %, whilst water vapour permeability increased from 12.91 g/cm 2 ·d to 16.18 g/cm 2 ·d. Simultaneously, the tensile strength and fracture elongation were improved from 5.43 MPa and 95.6 % to 5.96 MPa and 128 %. The thermal stability of composite packaging membranes was also enhanced by the incorporation of lotus leaf cutin.